2015
DOI: 10.1016/j.apergo.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Overload depending on driving experience and situation complexity: Which strategies faced with a pedestrian crossing?

Abstract: To cite this version:Julie Paxion, Edith Galy, Catherine Berthelon. Overload depending on driving experience and situation complexity: which strategies faced with a pedestrian crossing?. Applied Ergonomics, Elsevier, 2015, pp.343-349. 10 AbstractThe purpose of this study was to identify the influence of situation complexity and driving experience on subjective workload and driving performance, and the less costly and the most effective strategies faced with a hazard pedestrian crossing. Four groups of young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The workload generated by the driving activity can also explain why young drivers have been found to be disproportionately involved in road accidents, despite the introduction of a three-year probationary period after the obtention of the driving license. Learner drivers have been found to have a lower threshold of overload (Paxion, Galy and Berthelon 2015), probably owing to their lack of automated routines (Amalberti 1996;Cegarra and Hoc 2006;De Craen et al 2008;De Waard 1996) and the higher cognitive cost of driving (Damm et al 2011). Because of this low level of automatization, they have greater difficulty implementing the relevant strategies and allocate fewer resources to germane load, even if the task is simple and performed in a favourable context.…”
Section: Introductionmentioning
confidence: 99%
“…The workload generated by the driving activity can also explain why young drivers have been found to be disproportionately involved in road accidents, despite the introduction of a three-year probationary period after the obtention of the driving license. Learner drivers have been found to have a lower threshold of overload (Paxion, Galy and Berthelon 2015), probably owing to their lack of automated routines (Amalberti 1996;Cegarra and Hoc 2006;De Craen et al 2008;De Waard 1996) and the higher cognitive cost of driving (Damm et al 2011). Because of this low level of automatization, they have greater difficulty implementing the relevant strategies and allocate fewer resources to germane load, even if the task is simple and performed in a favourable context.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to Session B, the mental workload was reduced by 52.57% for Session A, and 27.73 % for Session C. This finding is consistent with the emphasized findings by Verwey [6] stating that a driving situation constitutes the major determinant of the mental workload of drivers. Similarly, Paxion [11] reported that an increase of subjective workload was globally observed when the situation complexity increased, with a tendency to higher self-assessment of the workload in very complex situation than in the simple one. It is anticipated in this study that city driving will score the highest workload, however, the result is contradict which it is probably due to lack complexity of the traffic density of the city during the experimental session.…”
Section: Discussionmentioning
confidence: 99%
“…An urban environment with heavy traffic, dense roadside scenery and many potential turns will contribute to a driver's cognitive load much more than a rural environment light traffic, sparse roadside scenery and few turns (Paxion, Galy, & Berthelon, 2015). Therefore, engaging in secondary tasks while driving in a complex road environment carries a higher risk of collision than doing so in a simple road environment.…”
Section: Objectivesmentioning
confidence: 99%